HIV Incidence by Male Circumcision Status From the Population-Based HIV Impact Assessment Surveys—Eight Sub-Saharan African Countries, 2015–2017. (1st August 2021) - Hines, Jonas Z.; Sachathep, Karampreet; Pals, Sherri; Davis, Stephanie M.; Toledo, Carlos; Bronson, Megan; Parekh, Bharat; Carrasco, Maria; Xaba, Sinokuthemba; Mandisarisa, John; Kamobyi, Royd; Chituwo, Omega; et al.
Abstract : Background: Male circumcision (MC) offers men lifelong partial protection from heterosexually acquired HIV infection. The impact of MC on HIV incidence has not been quantified in nationally representative samples. Data from the population-based HIV impact assessments were used to compare HIV incidence by MC status in countries implementing voluntary medical MC (VMMC) programs. Methods: Data were pooled from population-based HIV impact assessments conducted in Eswatini, Lesotho, Malawi, Namibia, Tanzania, Uganda, Zambia, and Zimbabwe from 2015 to 2017. Incidence was measured using a recent infection testing algorithm and analyzed by self-reported MC status distinguishing between medical and nonmedical MC. Country, marital status, urban setting, sexual risk behaviors, and mean population HIV viral load among women as an indicator of treatment scale-up were included in a random-effects logistic regression model using pooled survey weights. Analyses were age stratified (15–34 and 35–59 years). Annualized incidence rates and 95% confidence intervals (CIs) and incidence differences were calculated between medically circumcised and uncircumcised men. Results: Men 15–34 years reporting medical MC had lower HIV incidence than uncircumcised men [0.04% (95% CI: 0.00% to 0.10%) versus 0.34% (95% CI: 0.10% to 0.57%), respectively; P value = 0.01]; whereas among men 35–59 years, there was no significant incidence difference [1.36% (95% CI: 0.32% to 2.39%) versus 0.55% (95% CI: 0.14% to 0.67%), respectively; P value = 0.14]. Discussion: Medical MC was associated with lower HIV incidence in men aged 15–34 years in nationally representative surveys in Africa. These findings are consistent with the expected ongoing VMMC program impact and highlight the importance of VMMC for the HIV response in Africa.